I like what you are saying, but only if i feel safe: Psychological safety moderates the relationship between voice and perceived contribution to healthcare team effectiveness - Weiss, Mona; Morrison, Elizabeth W.; Szyld, Demian (Frontiers in Psychology, 2023)
Are nurses who voice work-related concerns viewed as positive contributors to a team? We propose that the extent to which healthcare professionals consider voice by nurses as helpful for the team depends on how psychologically safe they feel. Specifically, we hypothesized that psychological safety moderates the relationship between voice of a lower ranking team member (i.e., a nurse) and perceived contribution by others, such that voice is more likely to be seen as valuable for team decision-making when psychological safety is high but not when it is low. We tested this hypothesis with a randomized between-subjects experiment using a sample of emergency medicine nurses and physicians. Participants evaluated a nurse who either did or did not speak up with alternative suggestions during emergency patient treatment. Results confirmed our hypothesis: At higher levels of psychological safey the nurse’s voice was considered as more helpful than withholding of voice for team decision-making. This was not the case at lower levels of psychological safety. This effect was stable when including important control variables (i.e., hierarchical position, work experience, gender). Our results shed light on how evaluations of voice are contingent on perceptions of a psychologically safe team context.